LncRNA‐HOTAIR promotes endothelial cell pyroptosis by regulating the miR‐22/NLRP3 axis in hyperuricaemia. Issue 17 (22nd July 2021) - Chi, Kun; Geng, Xiaodong; Liu, Chao; Zhang, Yang; Cui, Jie; Cai, GuangYan; Chen, Xiangmei; Wang, Fangfang; Hong, Quan
Abstract: Long non‐coding RNA (lncRNA) plays an important role in the renal inflammatory response caused by hyperuricaemia. However, the underlying molecular mechanisms through which lncRNA is involved in endothelial injury induced by hyperuricaemia remain unclear. In this study, we investigated the regulatory role of lncRNA‐HOTAIR in high concentration of uric acid (HUA)–induced renal injury. We established hyperuricaemia mouse model and an in vitro uric acid (UA)–induced human umbilical vein endothelial cell (HUVEC) injury model. In HUA‐treated HUVECs and hyperuricaemia mice, we observed increased HOTAIR and decreased miR‐22 expression. The expression of pyroptosis‐associated protein (NLRP3, Caspase‐1, GSDMD‐N, GSDMD‐FL) was increased. The release of LDH, IL‐1β and IL‐18 in cell supernatants and the sera of model mice was also increased. The proliferation of HUVECs stimulated by HUA was significantly inhibited, and the number of TUNEL‐positive cells in hyperuricaemia mouse kidney was increased. Bioinformatics analysis and luciferase reporter and RIP assays confirmed that HOTAIR promoted NLRP3 inflammasome activation by competitively binding miR‐22. In gain‐ or loss‐of‐function experiments, we found that HOTAIR and NLRP3 overexpression or miR‐22 knock down activated the NLRP3 inflammasome and promoted pyroptosis in HUA‐treated HUVECs, while NLRP3 and HOTAIR knockdown or a miR‐22 mimic exerted the opposite effects. Furthermore, in vivo experiments validated that HOTAIR knockdown alleviated renal inflammation in hyperuricaemia mice. In conclusion, we demonstrated that in hyperuricaemia, lncRNA‐HOTAIR promotes endothelial cell pyroptosis by competitively binding miR‐22 to regulate NLRP3 expression.